A Study of the Influence of an Intervention on Environmental Education/Awareness and Behavior on Middle School Students in the UAE - Abu Shamat, Reema Maher (2015)
The environmental issues have become a great concern for many nations recently. It is the vision of UAE and its wise government to address such problems and concerns to protect the environment and to preserve the natural resources of the country. Unfortunately environmental issues are not a subject under study in schools. This dissertation aims at finding the amount of awareness raised among middle school students about critical environmental concerns after a period of classes that lasted for two weeks. The students were pre-assessed through a test about environmental issues to measure their degree of awareness of the issue, and the next step was to provide instruction for them in a two weeks course about the environmental critical concerns. The students were given the test again to do it after their new knowledge, and the results of the two tests were compared. The students were given later a survey to have insights about their opinions about the whole process of introducing environment based course content into their school curricula. The results of the study indicate noticeable increase in the students’ awareness about environmental issues after a two weeks intervention course about EE and the students reflected that they are interested in the practical side of the course. The study concluded that EE is essential and it should be integrated into schools’ curricula.